2009
DOI: 10.3136/fstr.15.147
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Obesity and Hypotriglyceridemic Properties of Coffee Bean Extract in SD Rats

Abstract: Coffee bean extract (CBE) was prepared from raw green coffee beans and contained 10.0% caffeine and 27.0% chlorogenic acid. Male Sprague-Dawley rats were fed a diet containing 1% CBE for 4 weeks. Although there was no difference in food intake between rats fed the control diet without CBE and those fed the CBE-containing diet, body weight gain and white adipose tissue weight were significantly decreased in CBE-fed rats than in control rats. The CBE-fed group exerted a significant and extreme reduction in serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 30 publications
(28 reference statements)
2
31
0
1
Order By: Relevance
“…On the other hand, considering the factorial arrangement of treatments, it was observed that all the rats receiving hyperlipidemic diets associated with integral coffee brews, regardless of the variety used, showed (P <0.05) lower weight gain and a lower percentage of lipids in housing in relation to decaffeinated brew, but the same effect was not observed (P> 0.05) in the yield and protein percentage in the carcass. Several studies performed with caffeine, a substance present in the integral coffee have shown similar results to the present study reducing the weight gain (Tanaka et al 2009;Swithers et al 2010) and inhibition of the deposition of adipose tissue in rodents (Inoue et al 2006;Tanaka et al 2009;Franco et al 2011), despite its association with hyperlipidemic diets. Coffee brew did not influence the protein deposition and carcass yield of the rats.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…On the other hand, considering the factorial arrangement of treatments, it was observed that all the rats receiving hyperlipidemic diets associated with integral coffee brews, regardless of the variety used, showed (P <0.05) lower weight gain and a lower percentage of lipids in housing in relation to decaffeinated brew, but the same effect was not observed (P> 0.05) in the yield and protein percentage in the carcass. Several studies performed with caffeine, a substance present in the integral coffee have shown similar results to the present study reducing the weight gain (Tanaka et al 2009;Swithers et al 2010) and inhibition of the deposition of adipose tissue in rodents (Inoue et al 2006;Tanaka et al 2009;Franco et al 2011), despite its association with hyperlipidemic diets. Coffee brew did not influence the protein deposition and carcass yield of the rats.…”
Section: Resultssupporting
confidence: 89%
“…These data were similar to the study of Franco et al (2011), who found no difference between the percentages of protein in the rats that received caffeine and control groups. These effects could be related to the inhibition of lipogenesis and increased lipolysis (Tanaka et al 2009). Caffeine is known to inhibit the activity of the phosphodiesterase, increasing the serum levels of cAMP and reducing the activity of lipase, which leads to an increased rate of lipolysis (Butcher et al 1968).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Diet-induced obesity (DIO) models have been well established, and widely used to find effective functional foods for anti-obesity. In recent studies, many observations have been reported concerning the ingestion of certain functional foods or their components decreasing the accumulation of body fat and inhibiting the elevation of body weight (23)(24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…Coffee is one of the most commonly consumed beverages in the world that its beneficial effects on human health have been a subject of many studies [8][9][10][11][12]. One of the common traditional forms of coffee is green coffee extract (GCE) that prepared from green or raw (unroasted) coffee been.…”
Section: Introductionmentioning
confidence: 99%